2014
DOI: 10.3892/mmr.2014.2521
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR polymorphisms and serum cobalamin affect plasma homocysteine concentrations differentially in females and males

Abstract: A total of 523 subjects (297 females and 226 males) from the Canary Islands Nutrition Study (ENCA) were studied in order to examine the effect of the MTHFR 677C>T, 1298A>C and 1793G>A polymorphisms, adjusted for age, serum (S)‑folate and S‑cobalamin levels, on total plasma homocysteine concentrations (tHcy). Genotyping was performed with Pyrosequencing® technology. The MTHFR 677T‑allele was associated with increased tHcy concentrations only in males (P=0.005). The MTHFR 1298C‑allele was found to be associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Numerous factors can affect the total plasma homocysteine (tHcy) levels in human plasma, such as gender (woman have lover tHcy than men), nutrition habits (diet deficient in folate, vitamin B 6 and B 12 leads to increment of tHcy), lifestyle habits (smoking, alcohol consumption, sedentary way of living) (Naik et al 2007;Nagele et al 2011;Nilsson et al 2014;Nygård et al 1995;Hildebrandt et al 2015;Jung et al 2015).…”
Section: Basic Mechanisms In Development Of Hyperhomocysteinemiamentioning
confidence: 99%
“…Numerous factors can affect the total plasma homocysteine (tHcy) levels in human plasma, such as gender (woman have lover tHcy than men), nutrition habits (diet deficient in folate, vitamin B 6 and B 12 leads to increment of tHcy), lifestyle habits (smoking, alcohol consumption, sedentary way of living) (Naik et al 2007;Nagele et al 2011;Nilsson et al 2014;Nygård et al 1995;Hildebrandt et al 2015;Jung et al 2015).…”
Section: Basic Mechanisms In Development Of Hyperhomocysteinemiamentioning
confidence: 99%
“…Another limiting factor is the small subset of SNPs selected for analysis. The 5 SNPs were selected because they are documented genetic determinants of circulating homocysteine concentrations (36)(37)(38), and homocysteine was a metabolite shown to be higher in astronauts with vision changes after longduration spaceflight (3). Ideally, SNPs of all enzymes of the 1-carbon pathway would have been studied.…”
Section: Markermentioning
confidence: 99%
“…The results of adult patients with epilepsy were contradictory (Dinç & Schulte, ). Some prior studies have also found that the MTHFR C677T mutation determined HHcy in patients with epilepsy receiving valproic acid (Ono, Sakamoto, Mizoguchi, & Sakura, ; Yoo & Hong, ), and the MTHFR 677T allele was found to be associated with increased Hcy levels only in males (Nilsson et al, ), suggesting that sex differences in a gene–drug interaction may lead to the changes of homologous system, which may provide reasonable explanations for conflicting results, and thus, further studies are needed to verify our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The results of adult patients with epilepsy were contradictory (Dinç & Schulte, 2018). Some prior studies have also found that the MTHFR C677T mutation determined HHcy in patients with epilepsy receiving valproic acid (Ono, Sakamoto, Mizoguchi, & Sakura, 2002;Yoo & Hong, 1999), and the MTHFR 677T allele was found to be associated with increased Hcy levels only in males (Nilsson et al, 2014), suggesting that sex differences in a gene-drug interaction may lead to the changes of homologous system, which may provide rea- were given to patients based on their severity and type of mood episode (manic, depression, or mixed). However, we did not collect information on the corresponding drugs in different mood phase, as well as information on different dosage, duration of treatment, or in combination with other drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation